Pengaruh Pemberian Pakan Dengan Kandungan Protein Berbeda Terhadap Pertumbuhan Ikan Nila (Oreochromis niloticus) - Aulia (Jurnal Ilmu Pertanian dan Perikanan, 2025)
This study aimed to determine the effect of different protein levels in feed on the growth performance of Nile tilapia (Oreochromis niloticus). The experiment was conducted at the Fish Hatchery Center (BBI) of Sleman Regency for 45 days using a completely randomized design (CRD) consisting of three protein levels—25%, 30%, and 35%—each with three replications. Observed parameters included weight gain, specific growth rate (SGR), feed conversion ratio (FCR), and survival rate (SR). The results showed that different protein levels significantly affected the growth of Nile tilapia (p < 0.05). The feed containing 30% protein produced the highest specific growth rate and the lowest FCR value. It can be concluded that a protein level of 30% in feed is optimal for promoting growth and feed efficiency in Nile tilapia.